1979
DOI: 10.1121/1.383072
|View full text |Cite
|
Sign up to set email alerts
|

Signature information in the song of the humpback whale

Abstract: This report tests the hypothesis that individual humpback whales (Megaptera novaeangliae) can be recognized and discriminated from other individuals on the basis of the ’’cry’’ vocalization. Multivariate discriminant analyses, based on six measurable variables, were used to examine intra- and interindividual differences in the ’’cries’’ from several individuals. Cries between themes of one song are very different, whereas those between songs of one individual are similar. Results show a high degree of discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…There have also been studies of the characteristics of the song units, quantifying frequency characteristics and duration of the sounds (e.g., Hafner et al, 1979;Helweg et al, 1998;MacKnight et al, 2001). Frequency and temporal characteristics of migrating humpback whale social sounds have also been described previously by Dunlop et al (2007), who found 34 discrete social sound types ranging in frequency from 40 Hz to 3 kHz, and in duration from 0.1 to 3.5 s. These sounds were recorded from humpback whales migrating along the east coast of Australia.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been studies of the characteristics of the song units, quantifying frequency characteristics and duration of the sounds (e.g., Hafner et al, 1979;Helweg et al, 1998;MacKnight et al, 2001). Frequency and temporal characteristics of migrating humpback whale social sounds have also been described previously by Dunlop et al (2007), who found 34 discrete social sound types ranging in frequency from 40 Hz to 3 kHz, and in duration from 0.1 to 3.5 s. These sounds were recorded from humpback whales migrating along the east coast of Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Using stepwise DFA, calls were classified to the correct individual and age class well above the level of classi fication expected by random chance. To our knowledge, this is the first quantitative assessment of acoustic variation among individuals using a stereotyped social call produced throughout the year by all individuals (Parks et al 2011) and represents only the second such ana lysis of individuality in a stereotyped call of any mysticete whale (Hafner et al 1979). As in studies of terrestrial mammals (Reby et al 1998, Gamba et al 2012), a combination of measurements from the fundamental frequency and the formants of the calls were effective for discrimination among individuals and groups.…”
Section: Discussionmentioning
confidence: 78%
“…This applies to all pinniped species that have been tested (Insley et al 2003): sub-Antarctic fur seals Arctocephalus tropicalis (Charrier & Harcourt 2006), Australian sea lions Neophoca cinerea (Gwilliam et al 2008), Weddell seals Leptonychotes weddellii (Van Opzeeland et al 2012) and several cetacean species including humpback whales Megaptera novaeangliae (Hafner et al 1979), killer whales Orcinus orca (Nousek et al 2006, Nichols et al 2010, Kremers et al 2012, sperm whales Physeter macrocephalus (Antunes et al 2011), and bottlenose dolphins Tursiops truncatus (Caldwell & Caldwell 1965, Sayigh et al 2007. Signature whistles of bottlenose dolphins are perhaps the most well-known of these examples, partially due to the dramatic differences in fundamental frequency contours among individuals (Janik & Sayigh 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessel noise has the potential to interfere with the complex vocal behavior of humpback whales, and thus could indirectly affect their population dynamics. Humpbacks produce a wide variety of vocalizations in many social contexts, which include the famous mating "songs" in their winter breeding grounds [4][5][6][7][8][9][10] as well as specialized "feeding calls" in their summer feeding grounds [11][12][13][14] that could serve as long-range assembly calls [2], likely coordinates group-feeding behavior and/or manipulate their prey (small schooling fish, [32]). Singing humpbacks are also known to modify their vocal behavior as a direct consequence of the vocal behavior of other humpbacks [5,8,15], most readily evidenced in the convergence of song acoustic structure among populations of males across each breeding season.…”
Section: Introductionmentioning
confidence: 99%